Design of a LP, RHCP and LHCP Polarization-Reconfigurable Holographic Antenna - Mei Li; Ming-chun Tang; Shaoqiu Xiao (IEEE Access, 2019)
In this paper, the feasibility of utilizing the microwave hologram to realize the high-gain radiation with polarization agility performance is investigated, and an effective method to design the polarization-reconfigurable holographic antenna is presented. By utilizing a polarization-insensitive hologram as the leaky-wave radiating structure and an appropriately designed, embedded, polarization-reconfigurable feeding launcher to control the polarization state of the radiating leaky waves, a polarization-reconfigurable holographic antenna with broadside radiation and linearly polarized (LP), right-hand circularly polarized (RHCP), and left-hand circularly polarized (LHCP) polarization diversity is successfully achieved. The simulation results demonstrate that the proposed antenna exhibits pencil beams with aperture efficiency up to 28.3% for the three polarization states. Meanwhile, the stable gain performance with peak gain above 17.5 dBi and gain fluctuation less than 1.7 dB is obtained for the three reconfigurable polarization states. For verification, a prototype was fabricated and tested to validate the proposed design concept. Moreover, the working mechanism is investigated.